Analysis of Covid-19 Vaccination Coverage in The Elderly in The Work Area of Cijayanti Puskesmas - Fitria Istina Dewi (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
The elderly (elderly) is one of the groups that are susceptible to being infected with Corona Virus Diseases 19 (Covid 19). Therefore, the elderly group is a priority group to get the Covid 19 vaccination. This study aims to describe and analyze the scope of the implementation of the COVID-19 vaccination program for the elderly in the Cijayanti Health Center work area which is still low. This research is a descriptive study with a qualitative approach. Data collection was carried out by in-depth interviews with midwives as the holder of the immunization program as the main informant, the doctor as the head of the vaccinator team, the holder of the elderly program, the Cijayanti, and Bojong Koneng village offices, and 10 elderly people. The achievement of the elderly vaccination at the Cijayanti Health Center was only 10.8% of the total number of elderly people. There are several obstacles in collecting data on elderly who are willing to be vaccinated because of the influence of the environment, both from their immediate family/children and from the surrounding community. Environmental factors, namely family support, community leaders, religious leaders greatly influence the participation of the elderly in covid vaccination 19.